1, 2-Dichloroethane induced nephrotoxicity through ROS mediated apoptosis in vitro and in vivo. Issue 5 (27th July 2015) - Li, Wenxue; Chen, Liping; Su, Yiwei; Yin, Hua; Pang, Yaqin; Zhuang, Zhixiong
Graphical Abstract: Abstract: 1, 2-Dichloroethane (DCE) is a ubiquitous occupational environmental contaminant. Subacute exposure of DCE could cause severe toxic encephalopathy. However, the toxicity of DCE on kidney and the molecular mechanism still remain elusive. To address this issue, we established a DCE-exposed animal model by inhalation in SD rats and used human embryonic kidney 293 (HEK293) cells in in vitro tests. We showed that the kidney/weight ratios were obviously higher in DCE-exposed groups than that in the control group. The renal distal tubules and distal convoluted tubule of rats treated with 577 ppm and 1000 ppm DCE obviously appeared abnormal. Moreover, apoptotic cells were found in the renal distal tubules from 1000 ppm DCE-exposed group. The antioxidant capacity was decreased and the levels of lipid peroxidation were increased in the kidney in exposure groups. In in vitro tests, we observed that there was no obvious toxicity in cells treated with DCE alone. However, over-expression of CYP2E1 or addition of S9 could remarkably increase the generation of ROS in HEK293 cells treated with DCE and decrease cell proliferation, even induce cell apoptosis. Antioxidant N -acetyl-l -cysteine (NAC) pre-treatment could inhibit the generation of ROS and alleviate cell apoptosis induced by DCE in the presence of an extra-metabolic system. Taken together, our findings provide direct evidence that excessive ROS generation may be the cause of the apoptosis effects induced by 1, 2-dichloroethane on the kidney.